(3JWHjb JYde fbGd bGFe Ydi GdESJQGJjLjGJ GdHUQjI dJfejI GdGfJHGg GdeTJQc dOi WdGH Phi GVWQGH Wja GdJhMO HOhdI GdEeGQGJ GdYQHjI GdeJMOI (B/ s - (3hdjO SjO eMehO eMeOs; (3SgjQ eMehO Cejf (B: s; (3WGQb YHOGdefYe MLGRi (B: s ((3GdbGgQI (B: s (3hdjO SjO eMehO eMeO (B: s, 2021)
(3gOa GdHMK HjGf CKQ JWHjb JYde fnbGd bGFe Ydi GSJQGJjLjGJ HUQjI (B((3UhQI eY eKjQ fUi(B. (3h UhQI eY eKjQ fUi h daXi(B) (3ai JfejI GdGfJHGg GdeTJQc dOi GdWdGH Phi GVWQGH Wja GdJhMO HOhdI GdEeGQGJ GdYQHjI GdeJMOI; h Je Pdc ef NdGd JMOjO bGFeI GdegGQGJ GdJi JfGSH GdWdGH Phi GVWQGH Wja GdJhMO(B: (3h HfGA JWHjb JYde bGFe Ydi GdESJQGJjLjGJ GdHUQjI(B: (3Je JbSje GdYjfI Edi eLehYJjf JLQjHjJjf GdChdi; YOO cd eLehYI (B(5) (3WdGH; GdeLehYI GdJLQjHjI GdChdi GSJNOeJ ESJQGJjLjI HUQjI (B((3UhQI eY eKjQ fUi(B): (3GdeLehYI GdJLQjHjI GdKGfjI(B: (3GSJNOeJ ESJQGJjLjI HUQjI (B((3UhQI eY eKjQ fUi h daXi(B): (3h Je JWHjb COhGJ GdHMK GdeJeKdI ai ebjGS GdGfJHGg GdeTJQc Ydi CaQGO GdeLehYJjf(B. (3h CTGQJ GdfJGFL Cf JWHjb GdJYde GdfbGd ShGA GdbGFe Ydi ESJQGJjLjI GdUhQI eY GdeKjQ GdfUi Ch ESJQGJjLjI GdUhQI eY GdeKjQ GdfUi h GddaXi cGf dg CKQ EjLGHi ai JfejI GdGfJHGg GdeTJQc dOi WdGH Phi GVWQGH Wja GdnJhMO HOhdI GdEeGQGJ GdYQHjI GdeJMOI HGdbOQ GdPi COi Edi GQJaGY OQLGJ GdeLehYJjf GdJLQjHjJjf ai GdbjGS GdHYOi Ydi ebjGS GdGfJHGg GdeTJQcs
(3GWQhMI (B((3eGLSJjQ(B) - (3GdLGenYI GdneUpQjI ddJnYdpe GdpEpdcJoQhpfi GdCgdjI (B- (3cdjI GdOQGSGJ GdJQHhjI (B- (3bSe JcfhdhLjG GdJYde GdEdcJQhfi s
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdGfJHGg GdeTJQcs; (3GdJYde GdfbGds; (3GdWdGH Phi GVWQGH Wja GdnJhMOs